2015
DOI: 10.1155/2015/614357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Malondialdehyde and Matrix Metalloproteinase‐9 on Progression of Carotid Atherosclerosis in Chronic Renal Disease with Cardiometabolic Syndrome

Abstract: Objective was to assess whether the concentration of malondialdehyde (MDA) as a marker of lipid peroxidation and serum concentration of matrix metalloproteinase-9 (MMP-9) are involved in the process of atherosclerosis in chronic kidney disease (CKD) patients nondialysis-dependent and those on peritoneal dialysis (PD), both with signs of cardiometabolic syndrome (CMS). Thirty CKD and 22 PD patients were included in a study. All observed patients were divided into three subgroups depending on the degree of ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Therefore, it promotes atherosclerosis [35, 36]. Consistent with previous studies [37, 38], our study suggests that elevated levels of MDA are correlated with carotid IMT. We further reveal that this association was closely observed in subjects with fewer metabolic syndrome components (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it promotes atherosclerosis [35, 36]. Consistent with previous studies [37, 38], our study suggests that elevated levels of MDA are correlated with carotid IMT. We further reveal that this association was closely observed in subjects with fewer metabolic syndrome components (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…Matrix metalloproteinase-9 also plays a critical role in the progression of atherosclerosis, loss of MMP-9 reduced the atherosclerotic burden throughout the aorta and impaired macrophage infiltration and collagen deposition [ 39 ]. Clinical studies have shown that MMP-9 levels in atherosclerosis vulnerable plaques were higher than in the nonvulnerable plaque and normal control groups, and that MMP-9 and atherosclerosis plaque vulnerability were positively correlated [ 40 ]. The results of animal experiments showed that the level of MMP-9 expression in the arterial and peripheral vessels of the atherosclerosis animal model was significantly higher, and the level of the elevation was positively correlated with the degree of atherosclerosis lesion; therefore, MMP-9 is one of the most important biological indexes for predicting plaque vulnerability in atherosclerosis [ 41 , 42 ].…”
Section: Markers In the Development Of Atherosclerosis Inflammatiomentioning
confidence: 99%
“…An extensive body of empirical data indicates that the MDA level in bodily fluids may be a reliable indicator of the extent of oxidative damage to cells in the body [5]. Available research indicates that MDA levels are increased due to cancer [6], atherosclerosis [7], diabetes [8], liver disease [9] and preeclampsia [10], as well as in smokers, while recent data suggest a strong link with periodontal disease [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%